Digital Competence, Social Capital and Emotional Intelligence on Teacher Performance with Job Satisfaction as Intervening Variables - Manalu, Nelly Chandrawati (Jurnal Pendidikan Indonesia, 2025)
The purpose of this study was to investigate the impact of digital competence, social capital, and emotional intelligence on teacher performance, with job satisfaction serving as an intervening factor. The type of research employed was a combination of quantitative and qualitative methods. The data analysis method employed was a structural equation model using the SmartPLS software. Data were obtained by distributing questionnaires to 389 high school teachers in Batam City. The data analysis method employed was a structural equation model using the SmartPLS software. The study's results found that digital competence, social capital, and emotional intelligence had a direct and significant positive effect on teacher job satisfaction. Second, digital competence, emotional intelligence, and job satisfaction had a direct and significant positive effect on teacher performance. In contrast, social capital did not have a direct significant effect on teacher performance. Third, job satisfaction fully mediated the effect of social capital and emotional intelligence on teacher performance, but job satisfaction did not mediate the effect of digital competence on teacher performance. In conclusion, digital competence, social capital and emotional intelligence had a positive effect on teacher performance, both directly and indirectly, through job satisfaction as an intervening variable. The implication is that increasing digital competence, social capital, and emotional intelligence simultaneously can encourage more optimal teacher performance, especially when job satisfaction is present as a variable that significantly mediates these influences.